The impact of green initiative announcements on the stock prices of selected publicly listed companies in the food and beverage industry in ASEAN-5 - Eguia, Samantha Nicole Fernandez (Animo Repository, 2023)
Companies are now held to higher standards and are expected to implement green initiatives aimed at reducing negative environmental impact and promoting sustainability. Through an event study, the researchers determined the impact of green initiative announcements, specifically concerning waste management and renewable energy, on the CAAR of the stock prices of selected publicly listed companies in the food and beverage industry in ASEAN-5 countries, namely, Indonesia, Malaysia, Philippines, Singapore, and Thailand from 2021 to 2022. The researchers adopted a causal, mixed-method research design and applied the total enumeration approach in determining the sample. With the use of Microsoft Excel and Jamovi, the researchers computed the CAAR and tested for its significance through a one-sample two-tailed t-test. The findings indicated that the CAAR is significant and negative 5, 6, and 8 days (CAAR = -0.79% -0.65% -0.53%, p < .05) before the announcement date. Waste management green initiatives also had a significant and negative CAAR 8 and 10 days (CAAR = -0.79% -0.41%, p < .05) and 9 days (CAAR = -0.83%, p < .01) before the announcement date. Meanwhile, renewable energy green initiatives had no significant impact during the event window (p < .05). The findings demonstrate various market responses to the different types of green initiatives and can aid in advancing knowledge of how these can influence market reactions and investor sentiments.